Evidence of cellular nicotinic receptor desensitization in rats exhibiting nicotine-induced acute tolerance - Robinson, Susan E.; James, John R.; Lapp, Laura N.; Vann, Robert E.; Gross, Daniel F.; Philibin, Scott D.; Rosecrans, John A. (Psychopharmacology, 2006)
Individuals vary in their susceptibility to nicotine addiction. However, there is little evidence that behavioral sensitivity to nicotine is dependent upon the functional state of nicotinic cholinergic receptors (nAChRs). To determine the relationship between in vivo pharmacological desensitization (in other words, acute tolerance) and brain regional nAChR function. Male Sprague-Dawley rats, trained to discriminate nicotine (0.4 mg/kg free base) from saline in a two-lever drug discrimination task, were tested for the development of acute tolerance. Rats were injected with 0.4 mg/kg nicotine, tested for nicotine discrimination for 2 min, then injected with the same dose of nicotine 90 min, 180 min, and 270 min after the first injection and tested for nicotine discrimination after each injection. These subjects were separated into two groups, desensitizers (DZ) and nondesensitizers (NDZ), based upon performance in the repetitive dosing drug discrimination paradigm. The sensitivity of nAChRs in specific brain regions of these two groups was assessed by the use of an 86Rb+ efflux assay using synaptosomes prepared from the frontal cortex, hippocampus, striatum, and "thalamus," which included the midbrain and hypothalamus as well as the thalamus. The nicotine-induced increase in 86Rb+ efflux was significantly greater in NDZ as compared to DZ in the "thalamus." There was no statistically significant difference in the effects of nicotine in the frontal cortex, hippocampus, and striatum of these two groups. A significant correlation was observed between thalamic 86Rb+ efflux and the rate of behavioral desensitization of individual rats. These findings are consistent with the concept that the production of acute tolerance by nicotine in vivo correlates directly with its ability to induce nAChR desensitization at the cellular level.